Improving the Electricity Generation in a Photovoltaic Panel Including Finned-Pcm Systems Using Time-Dependent Numerical Simulations - Castillo-Del Barrio, E; Gonzalez-Andres, A; Diaz-Moreno, F (Elsevier Ltd, 2025)
This study investigates a passive thermal management strategy for photovoltaic (PV) by integrating a finned phase change material (PCM) system to mitigate overheating and enhance energy efficiency. The research addresses the limitations of improving PCM thermal response and PV performance through the integration of metallic fins with varying geometric configurations and material distribution. A total of 27 configurations are analyzed under constant atmospheric conditions. The optimal design is then assessed under realistic day night cycles using climatic data from a semi-arid city in northern Chile (Vallenar). Numerical simulations are performed using the finite volume method implemented in OpenFOAM, with validation against published experimental and numerical results. The method is then applied to examine the thermal behavior and performance of the 27 finned PV-PCM configurations. In broad terms, incorporating metallic fins reduces the volume of PCM required while enhancing system efficiency. According to our findings, finned-PCM systems are a promising solution for passive thermal regulation of PV panels. The results show that the use of a 40 mm layer of CaCl2−6H2O PCM without fins increases the electricity generation by 10.1% in summer and 7.9% in winter, compared to a baseline case without thermal management. When aluminum fins are integrated into the PCM cavity, electricity generation increases by 11.4% in summer and 8.8% in winter while reducing the temperature of the PV panel by up to 24.3 °C under peak irradiance conditions. These findings highlight the potential of fin-enhanced PCM systems as effective, low-cost solutions for passive thermal regulation in solar technologies. © 2025 Elsevier Ltd